Microwave-Assisted Copper-Catalyzed Cross-Coupling Reaction of Thiols with Aryl Iodides in Water - Chen, Yi-An; Badsara, Satpal Singh; Tsai, Wan-Ting; Lee, Chin-Fa (Synthesis, 2015)
Microwave-promoted C–S bond formation from thiols and aryl iodides in the presence of a copper catalyst is reported. A combination of copper(II) oxide and 1,10-phenanthroline catalyzes this reaction. A variety of aryl iodides react smoothly with thiols to provide the corresponding aryl sulfides in good to excellent yields. Notably, the reactions proceed in water with a short reaction time (30 minutes). This system shows broad functional-group tolerance; amino, chloro, bromo, acetyl, and nitro groups are unaffected by the reaction conditions.
Keywords: microwave heating; copper; cross-coupling; thiols; aryl iodides; sulfides